2021
DOI: 10.1177/23993693211002216
|View full text |Cite
|
Sign up to set email alerts
|

Cancer therapy-induced hyponatremia: A case-illustrated review

Abstract: Hyponatremia is the most common electrolyte disorder in patients with cancer and is associated with significant morbidity and mortality. Innovation in cancer therapies has led to substantial improvement in cancer outcomes, but also to new therapy-related toxicities, including electrolyte disturbance. Improvement in clinicians understanding of hyponatremia may mitigate adverse outcomes and improve quality of life in cancer patients. In this case-illustrated review, we discuss the mechanisms underlying drug-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Hyponatremia is the most frequently encountered electrolyte and fluid disturbance, affecting up to 30% of hospitalized patients. 11 The first step in diagnosis begins with the categorization of the serum tonicity and the exclusion of pseudohyponatremia. Our patient was determined to have euvolemic hypotonic hyponatremia based on volume status, a low serum osmolality and an inappropriately high urine osmolality and sodium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyponatremia is the most frequently encountered electrolyte and fluid disturbance, affecting up to 30% of hospitalized patients. 11 The first step in diagnosis begins with the categorization of the serum tonicity and the exclusion of pseudohyponatremia. Our patient was determined to have euvolemic hypotonic hyponatremia based on volume status, a low serum osmolality and an inappropriately high urine osmolality and sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Between October 2019 and January 2020, the patient received nivolumab, a PD-1 inhibitor that has been associated with hyponatremia. 3 , 11 One study found that severe hyponatremia typically occurs within 1 year of ICI initiation 3 ; another reported onset as early as 9 days after initiation. 11 As the patient’s first episode of severe hyponatremia in November 2021 was noted 22 months after the discontinuation of nivolumab, we concluded that nivolumab was an unlikely trigger for the recurrent hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic approach to the diagnosis of hyponatraemia in patients with cancer is complicated and needs awareness of pathophysiological processes related to both the tumour and the expanding compendium of anticancer therapies. SIADH is the most common underlying process in most cancer or cancer therapy-associated hyponatraemia 7…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hyponatremia is higher with anti-CTLA-4 therapy compared with PD-1 or PD-L1 inhibitors. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The risk of hyponatremia is higher with anti-CTLA-4 therapy compared with PD-1 or PD-L1 inhibitors. 14 In a retrospective observational study done on approximately 2500 patients with different cancers receiving ICIs, it was found that hyponatremia is the most common side effect occurring in 62% of patients with sodium level <134 mEq/dL, and out of those, 6% developed severe hyponatremia with sodium level <124 mEq/dL. 8 Another study shows that hypophysitis has an incidence of 10% to 17% from the anti-CTLA-4 Ipilimumab, whereas a combination of Ipilimumab and Nivolumab induced hypophysitis in 13% of patients.…”
Section: Discussionmentioning
confidence: 99%